STRATEGI OPTIMALISASI MANAJEMEN KESISWAAN DAN SARANA PRASARANA DALAM MENINGKATKAN LITERASI SISWA DI SDN GILI ANYAR - Argatya Abid Nur Fadhlurrahman; Ayu Maghfirah Widiyati; Nurul Maryani; Fiki Riehaz Zuhdi; Andika Adinanda Siswoyo (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This study aims to identify problems in student management and infrastructure at SDN Gili Anyar and propose solutions to improve student literacy. The method used is descriptive qualitative with data collection techniques through observation, interviews, and literature studies. The study results show that student literacy at SDN Gili Anyar faces significant challenges due to the lack of library facilities, which have been damaged and unusable for the past three years. In addition, there are no outstanding academic programs supporting student literacy development, although efforts to build student character have been going well. As a solution, this study proposes two alternatives: reading corners and the School Literacy Movement (GLS). Reading corners, according to the study by Anugrah et al. (2022), can serve as a substitute for libraries by utilizing classroom corners to store reading materials. Meanwhile, GLS, as highlighted by Khusna et al. (2022), involves the habit of reading for 15 minutes before lessons begin to foster students' interest in reading. The implementation of these two solutions requires support from teachers and parents in providing books and cultivating reading habits at home. This study emphasizes the importance of optimizing student management and infrastructure to enhance student literacy. Literacy, as the foundation of learning, plays a crucial role in developing students' academic potential and better character in the future.